Antibacterial activity of natural spices on multiple drug resistant Escherichia coli isolated from drinking water, Bangladesh - Islam Rezuanul; Parvez Anowar; Rahman Shahedur; Khan Mahboob (BMC, 2011)
Abstract Background Spices traditionally have been used as coloring agents, flavoring agents, preservatives, food additives and medicine in Bangladesh. The present work aimed to find out the antimicrobial activity of natural spices on multi-drug resistant Escherichia coli isolates. Methods Anti-bacterial potentials of six crude plant extracts (Allium sativum, Zingiber officinale, Allium cepa, Coriandrum sativum, Piper nigrum and Citrus aurantifolia) were tested against five Escherichia coli isolated from potable water sources at kushtia, Bangladesh. Results All the bacterial isolates were susceptible to undiluted lime-juice. None of them were found to be susceptible against the aqueous extracts of garlic, onion, coriander, pepper and ginger alone. However, all the isolates were susceptible when subjected to 1:1:1 aqueous extract of lime, garlic and ginger. The highest inhibition zone was observed with lime (11 mm). Conclusion Natural spices might have anti-bacterial activity against enteric pathogens and could be used for prevention of diarrheal diseases. Further evaluation is necessary.